Evapotranspiração máxima do tomate e do pimentão em estufa plástica em função da evaporação no piche e outras variáveis meteorológicas e fenométricas - Pivetta, Carina Rejane (2007)
Protected cropping is an alternative cropping system to produce vegetables outside the field growing season because of increase in yield, quality, and price. Evapotranspiration is an important parameter for managing irrigation inside plastic houses. In order to improve the efficiency of irrigations, relationships between meteorological variables and plant growth parameters need to be known to develop models for estimating crops water demand. The objective of this study was to estimate maximum evapotranspiration (ETm) of sweet pepper and tomato inside plastic house as a function of evaporation measured with Piche evaporimeter exposed to solar radiation (Epi) with and without other meteorological variables easily measured during the spring growing season in Santa Maria, RS, Brazil. The experiment was carried out inside a 240 m2 plastic house. Daily ETm (measured with drainage lysimeters), Epi, air temperature, vapor pressure deficit (D), leaf area index (LAI), plant height (AP), and leaf number (NF) were measured. Using regression analyses, models were fit to estimate ETm using sweet pepper data collected during spring 2005, and tomato data collected on even days of set collected during spring 2005. In the multiple regression analysis only models with parameters significant at 5 % by t test and coefficient of determination (r2) >0,8 were selected. For sweet pepper, models were evaluated with independent data collected in an experiment conducted from 23/08 to 07/12/2006. For tomato, models were evaluated with independent data collected on add days of the 2005 experiment. Statistics used for model evaluation were regression analyses between observed and estimated data, root mean square error, and accuracy, agreement and confidence indices. Results showed that it is possible to estimate ETm of sweet pepper and tomato crops with acceptable accuracy to perform irrigation inside plastic greenhouse using models that take into account Epi and at least one plant growth parameter, which for sweet pepper LAI was better than NF and AP. Including AP resulted in intermediate model performance compared to LAI and NF for estimating ETm in sweet pepper, whereas including an additional meteorological variable, besides Epi, usually led to a small improvement in model fitting and model performance in this crop. For estimating ETm in tomato, models with the parameter AP should be preferred. Including D measured at 9h in the models with Epi and AP or NF or LAI improved ETm estimates. When one has only a maximum and minimum thermometer, AP or NF, ETm of sweet pepper can also be estimated using daily temperature amplitude and air temperature measured at 9h